Adoption of mobile money and financial inclusion in the Gambia: Evidence from small businesses and households - Lamin Saidyjeng; Alasana Gitteh; Modou Lamin Fatajo; Musa Nasso (Privietlab, 2026)
This study examines the structural mechanisms through which mobile money adoption translates into financial inclusion outcomes in The Gambia. Moving beyond binary measures of access, this study investigates how and for whom mobile money generates tangible economic benefits. A sequential explanatory mixed methods design was employed, comprising surveys of 384 households and 152 small businesses, followed by semi-structured interviews. Structural equation modelling (SEM) was used to test a conceptual model in which perceived utility, social influence, and facilitating conditions predict adoption intensity, which then mediates financial resilience and operational efficiency. The results show that perceived utility and strong agent networks are the strongest predictors of deep adoption. Adoption intensity strongly mediates gains in household financial resilience and small-business operational efficiency. A critical finding is a usage plateau: despite mobile money’s effectiveness as a payment bridge over the digital divide, the connection to formal credit remains weak, constraining deeper financial inclusion in the long run. Policy should therefore shift from promoting access to enabling qualitative usage for example, by using transaction data for credit scoring and ensuring equitable service quality so that mobile money becomes a platform for comprehensive financial empowerment.